Analysis of Conventional and Islamic Monetary Policy Transmission on Inflation and Economic Growth - Muhammad Syariful Anam; Rifda Nabila; Arna Asna Annisa; Rina Rosia (International Journal of Islamic Business and Economics (IJIBEC), 2022)
This empirical study aims to analyze the transmission of conventional and sharia monetary policies to inflation (CPI) and economic growth (GDP) using the instruments of SBI, PUAB, SBIS, and PUAS for the period 2002 to 2020. The data in this study are secondary data obtained from the Indonesian National Agency for Finance. Center for Statistics (BPS) and Indonesian Economic and Financial Statistics (SEKI) BI. The analytical tool used is the VAR/VECM approach. Based on the analysis that has been carried out, several findings were obtained: first, in the short term, CPI is influenced by SBI, PUAB, and SBIS, while GDP is influenced by SBI, PUAB, SBIS, and PUAS. Second, in the long term, CPI is significantly influenced by SBI, PUAB, SBIS, and PUAS, while GDP is only influenced by SBI and PUAS variables. Third, in the IRF analysis, the variables of SBI, PUAB, and SBIS were responded negatively by the CPI, while PUAS was responded to positively by the CPI. The variables PUAB, SBIS, and PUAS responded positively by GDP, while GDP responded negatively to SBI. Fourth, from the results of the FEVD analysis, the conventional channel variable has a greater contribution to influencing inflation (CPI) than the sharia channel variable. Meanwhile, the sharia channel variable has a greater contribution to economic growth (GDP) compared to the conventional channel variable.